KEMAMPUAN GELATIN TULANG SAPI SEBAGAI BAHAN PENGIKAT TERHADAP KUALITAS FISIK SOSIS AYAM (Ability of Bovine Bone Gelatin As a Binder on The Physical Quality of Chicken Sausage) - Andi Nurul Mukhlisah; Setiawan Putra Syah; Weny Dwi Ningtiyas; Muhammad Irfan; Andi Citra Septaningsih; Suriansyah Suriansyah (JURNAL NUKLEUS PETERNAKAN, 2026)
The purpose of this study was to determine the physical quality of chicken sausage made with the addition of gelatin from beef bones. In addition, it can provide information for the meat processing industry as a meat product thickener. This study used bovine femur bones to produce gelatin. A completely randomized design was used, consisting of 5 treatments without gelatin addition (0%), gelatin addition (3%), gelatin addition (6%), gelatin addition (9%), and gelatin addition (12%), with 4 replicates. The variables observed were physical qualities such as water-binding capacity, elasticity, pH, cooking shrinkage, and hardness. The results showed that the addition of gelatin had a significant effect (P<0.05) on the water-binding capacity, elasticity, cooking shrinkage, and hardness of chicken sausages. The best results were found at a gelatin addition level of 6%, which improved the physical quality of chicken sausage. Gelatin increased water-holding capacity, maintained pH, and made the texture more flexible, elastic, and tender. With its gel-forming properties, gelatin is effective as an additive to improve the quality of meat products.